Discovering novel immune-modulatory monosaccharides using high-throughput screening strategies - Alobaid, Meshal (2020)
Introduction: New strategies for immunomodulation and immunotherapy to fight infections, allergic diseases and cancer have shown real promise in recent years. Dendritic cells (DCs) are considered gatekeepers of the immune system and act as a bridge between innate and adaptive immune systems. Upon antigen uptake in peripheral tissues, DCs migrate to the lymph nodes and interact with T cells where they guide T cell polarisation towards distinct inflammatory or regulatory phenotypes. Their ability in shaping adaptive immune responses makes DCs ideal targets for immune modulation. The immune-instructive properties of DCs upon encountering T cells are dependent on their cytokine profile and the co-stimulatory molecules expressed. In this project, I used a high throughput screening strategy to investigate immune modulatory properties of a combinatorial library of immobilised synthetic monosaccharides with a particular focus on their ability to modulate key phenotypic and functional properties of human DCs. I also investigated the modulatory properties of these monosaccharides in particulate form, using gold nanoparticles (AuNPs) coated with monosaccharides, and studied their impact on DCs phenotype and function as well as identifying sugar moieties that enhance uptake of the AuNPs. Results: A selection of immobilised carbohydrates including 100%1-amino-1-deoxy--Dgalactose (Gal1), 100%2-amino-2-deoxy--D-galactose (Gal2), 90%2-amino-2-deoxy--Dgalactose+10%1-amino-1-deoxy--D-mannose (Gal2-Man1), 2-amino-2-deoxy--Dgalactose+10%2-amino-2-deoxy--D-mannose (Gal2-Man2), 40%1-amino-1-deoxy--Dmannose + 60%2-amino-2-deoxy--D-mannose (Man1-Man2) and 50%1-amino-1-deoxy-- D-galactose +50%2-amino-2-deoxy--D-galactose (Gal1-Gal2), significantly downregulated LPS induced CD40 expression, compared to LPS alone, upregulated CD274 but had no significant changes in the expression of CD86 compared to unconditioned LPS stimulated controls. This was accompanied by a significant decrease in the activity of key immune regulatory enzyme 2,3 indoleamine dioxygenase (IDO) and production of interleukin (IL)-12, a signature pro-inflammatory cytokine. Furthermore, DCs stimulated with the same combinations of carbohydrates showed a significant increase in production of prototypic regulatory cytokine IL-10. Collectively these data suggest an anti-inflammatory/regulatory phenotype for DCs treated with these carbohydrates. Furthermore, DCs conditioned with a selection of anti-inflammatory carbohydrates (Gal1-Gal2 and Gal1) induced naïve T cell polarisation towards regulatory phenotype while other carbohydrate combinations shown to increase IL-12 production (Man1-Man2, Gal2-Man1 and Gal2-Man2) induced T-helper 1 phenotype confirming the anti and prof inflammatory DC phenotypes respectively. Moreover, an increase in IL-17 and RORγt expression confirmed presence of TH17 in conditions treated with Gal1 and Gal1-Gal2 while a decrease in the latter was noted in Man1-Gal2. This was also confirmatory in the allergy module where Gal1-Gal2 maintained production of IL-17 and Man1-Gal2 had significant reduction in IL-17 clearly showing the carbohydrates potential in immunomodulation. Carbohydrate coated AuNPs showed differential uptake by DCs where 100%fucose, 100%mannose, 90%mannose+10%Galactose and 80%mannose+20%Galactose coated AuNPs had highest internalization. Flow cytometry showed increased lysosomal and endosomal localisation for AuNPs coated with 100%fucose over the other conditions compared to uncoated AuNPs. Investigations of the fate of the particles showed significant increased co-localization of AuNPs with lysosomes for 100%fucose, 80%fucose+20%galactose and 70%galactose+20%mannose compared to other conditions. On the other hand, co-localization of AuNPs with endosomes for 100%mannose was significantly higher than other conditions. An understanding of receptor mediated endocytosis (active uptake) and micropinocytosis (passive uptake) mechanisms was assessed using Methyl-β-cyclodextrins where there was a significant reduction of uptake between Methyl-β-cyclodextrins treated and untreated conditions suggesting the predominant mechanism of internalization of the AuNPs is active uptake. Conclusions: Collectively these observations show the potential immunomodulatory effects of immobilised monosaccharides in priming DCs and skewing immune responses towards different functional pro- or anti-inflammatory/regulatory phenotypes. It also provides insights into using monosaccharides to optimize cellular uptake of nanoparticles as well as guiding trafficking towards different intracellular compartments. This understanding could pave the way for utilising simple monosaccharides in the development of anti-inflammatory coatings for graft implants and reduction of chronic inflammatory and autoimmune responses as well as potent drug delivery platforms guided towards antigen delivery and RNA silencing therapies.